2021
DOI: 10.3390/rs13245081
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Influences of Natural and Anthropogenic Factors on Vegetation Changes Based on Geodetector: A Case Study in the Poyang Lake Basin, China

Abstract: Understanding the driving mechanism of vegetation changes is essential for vegetation restoration and management. Vegetation coverage in the Poyang Lake basin (PYLB) has changed dramatically under the context of climate change and human activities in recent decades. It remains challenging to quantify the relative contribution of natural and anthropogenic factors to vegetation change due to their complicated interaction effects. In this study, we selected the Normalized Difference Vegetation Index (NDVI) as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Best time lag changes are not influenced by a single factor but by the overall interaction effect between the vegetation type and soil texture factors. Previous studies indicated that the interaction effect of two factors was always greater than that of a single factor [53]. In this study, the interaction effect between the vegetation type and soil texture factors indicated enhancement.…”
Section: Time-lag Effects Of Climate Conditions On Npp With Vegetatio...supporting
confidence: 45%
See 1 more Smart Citation
“…Best time lag changes are not influenced by a single factor but by the overall interaction effect between the vegetation type and soil texture factors. Previous studies indicated that the interaction effect of two factors was always greater than that of a single factor [53]. In this study, the interaction effect between the vegetation type and soil texture factors indicated enhancement.…”
Section: Time-lag Effects Of Climate Conditions On Npp With Vegetatio...supporting
confidence: 45%
“…The Geodetector model is a new spatial statistical tool for exploring spatial heterogeneity and quantitatively evaluating the contribution of driving factors [53]. This tool comprises four modules, namely, factor detector, ecological detector, risk detector, and interaction detector.…”
Section: The Geodetector Modelmentioning
confidence: 99%
“…Geodetector (Microsoft, Redmond, Washington, DC, USA) is a set of statistical methods that detect spatial differentiation and reveal its driving forces, which can effectively detect the causes and mechanisms of spatial patterns of geographical elements [ 42 , 43 , 44 ]. We used the factor detection method of Geodetector to study the influencing factors of the spatial distribution equilibrium of two-tier medical and health resources in Taiyuan.…”
Section: Data Source and Methodologymentioning
confidence: 99%
“…The average strength of the explanatory power of natural factors on vegetation cover over the 21-year study period varied with temperature (0.216) > elevation (0.205) > soil clay content (0.172) > precipitation (0.163) > soil sand content (0.138) > slope (0.059) > slope orientation (0.014) ( Figure 6 ). Changes in vegetation cover are complex processes and are significantly influenced by human activities (land use type, GDP density, population density and distance from roads) [ 23 , 54 , 55 ]. Previous studies in Xinjiang have shown that human activities and active policies are the main influences on the regional vegetation cover [ 56 ].…”
Section: Discussionmentioning
confidence: 99%